2017
DOI: 10.1007/s00426-017-0947-6
|View full text |Cite
|
Sign up to set email alerts
|

Fleeting reliability in the dot-probe task

Abstract: In a dot-probe task, two cues-one emotional and one neutral-are followed by a probe in one of their locations. Faster responses to probes co-located with the emotional stimulus are taken as evidence of attentional bias. Several studies indicate that such attentional bias measures have poor reliability, even though ERP studies show that people reliably attend to the emotional stimulus. This inconsistency might arise because the emotional stimulus captures attention briefly (as indicated by ERP), but cues appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
84
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 60 publications
10
84
1
3
Order By: Relevance
“…While we previously found that FDOT threat bias one day after single-session CBT predicted clinical improvement, this observation was not replicated in this study. Recent work into the psychometric properties of the dot probe task suggests weak test-retest reliability, indicating that alternative measures of threat bias might be preferable (29). In line with this recommendation, we found that amygdala threat response was more sensitive to brief treatment than the behavioural measures used, leading to large effect sizes of d>1 and predicting clinical recovery.…”
Section: Discussionsupporting
confidence: 79%
“…While we previously found that FDOT threat bias one day after single-session CBT predicted clinical improvement, this observation was not replicated in this study. Recent work into the psychometric properties of the dot probe task suggests weak test-retest reliability, indicating that alternative measures of threat bias might be preferable (29). In line with this recommendation, we found that amygdala threat response was more sensitive to brief treatment than the behavioural measures used, leading to large effect sizes of d>1 and predicting clinical recovery.…”
Section: Discussionsupporting
confidence: 79%
“…Supporting that notion and the association between deprivation and attention bias away from threat found at follow up, the association between exposure to adversity and attention bias away from threat among adolescents, and not children, has already been documented (Weissman et al, 2019). Such results should be interpreted with caution due to the low stability of the attention bias measure in this study, considering that the utility of using the dot-probe has already been called into question due to its low-retest reliability (Chapman, Devue and Grimshaw, 2019).…”
Section: Discussionsupporting
confidence: 63%
“…One explanation might be the consistent use of a cuetarget onset-asynchrony of 100 ms. Although short CTOAs are recommended by numerous researchers to investigate shifts in covert attention (Cooper & Langton, 2006;Petrova et al, 2013;Stevens et al, 2011;Weierich et al, 2008), many dot-probe studies use longer CTOAs of typically 500 ms (see Chapman, Devue, & Grimshaw, 2017;Cooper & Langton, 2006, for a critical discussion of this standard). Therefore, the attentional bias might simply be too transient to be detectable at 500 ms after cue onset.…”
Section: Discussionmentioning
confidence: 99%